A N-heterocyclic carbene Ni(II) complex bearing bis(cyclopentadienyl) ligands as a precatalyst for the dehydrogenative silylation of alcohols with hydrosilanes. Issue 22 (27th May 2015) - Ohta, Hidetoshi; Miyoshi, Narumi; Sakata, Yoshihiro; Okamoto, Yuki; Hayashi, Minoru; Watanabe, Yutaka
Graphical abstract: Abstract: An air- and moisture-stable N -heterocyclic carbene Ni(II) complex bearing bis(cyclopentadienyl) ligands was found to be an effective precatalyst for the dehydrogenative silylation of alcohols with hydrosilanes. Various aryl and alkyl alcohols were silylated in the presence of the Ni catalyst (1–4 mol %) in toluene at 110 °C, giving the corresponding silyl ethers in 59–99% isolated yields. Time-course studies revealed that the reaction has an induction period, during which the Ni(II) complex would be reduced to catalytically active Ni(0) species.